2014
DOI: 10.1074/mcp.o113.032748
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Arginine Methylation Sites in Human Cells Reveals Dynamic Regulation During Transcriptional Arrest

Abstract: The covalent attachment of methyl groups to the side-chain of arginine residues is known to play essential roles in regulation of transcription, protein function, and RNA metabolism. The specific N-methylation of arginine residues is catalyzed by a small family of gene products known as protein arginine methyltransferases; however, very little is known about which arginine residues become methylated on target substrates. Here we describe a proteomics methodology that combines single-step immunoenrichment of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 74 publications
5
72
0
Order By: Relevance
“…In line with previous reports showing that ERα methylation is a dynamic process, requiring PRMT1 for methylation and JMJD6 arginine demethylase to remove the methylated moiety (56,57), global proteomic analysis also demonstrated that arginine methylation sites in human cells are regulated dynamically by an unknown Arg demethylase during transcriptional arrest (58). It is possible that the Arg demethylation process is a general event regulating cellular Arg methylation level.…”
Section: Methodssupporting
confidence: 69%
“…In line with previous reports showing that ERα methylation is a dynamic process, requiring PRMT1 for methylation and JMJD6 arginine demethylase to remove the methylated moiety (56,57), global proteomic analysis also demonstrated that arginine methylation sites in human cells are regulated dynamically by an unknown Arg demethylase during transcriptional arrest (58). It is possible that the Arg demethylation process is a general event regulating cellular Arg methylation level.…”
Section: Methodssupporting
confidence: 69%
“…The lack of study of this posttranslational modification to date may be due to the scarcity of PRMT substrates, to the intrinsic stability histone R methylation (which is seen as incompatible with a role in regulating cellular pathways), and to the lack of tools for detecting R methylation. Together with recent investigations (33)(34)(35), the present work dispels these earlier impressions, and raises histone R methylation changes in response to repeated cocaine to the rank of other more well-known histone posttranslational modifications implicated in the epigenetic basis of addiction.…”
Section: Discussionmentioning
confidence: 62%
“…Despite the prospective issues associated with sequence database search-derived methylpeptide identifications, the use of orthogonal methylpeptide validation in large scale methylation site discovery studies remains sporadic. Although several such studies have employed heavy-methyl SILAC (6,7,14,16) or other closely related methylpeptide-specific labeling techniques (12,13) to validate methylation sites, others have chosen to bypass orthogonal validation and to instead predominantly rely on the target-decoy approach to provide estimates for high stringency methylpeptide filtering criteria (4,5,8,9,15) or to inform manual data curation (see Table I) (10,11). This irregular use of orthogonal methylpeptide validation is a reflection of the fact that in-depth studies into methylpeptide FDRs have yet to be performed.…”
mentioning
confidence: 99%
“…Demonstrations of significantly enhanced methylation site discovery have, for example, been reported from samples generated via pan-specific antibody (8,13) and methyl-lysine binding domain-based (19) pulldowns of methylpeptides, analyzed on Orbitrap Elite and Q Exactive or Orbitrap Velos instruments, respectively, and from samples enriched for arginine-methylated peptides using hydrophilic interaction liquid chromatography (HILIC), analyzed on a Q Exactive instrument (6). Together these contemporary instrument platforms and analytical workflows have enabled thousands of novel methylation sites to be identified from hundreds of proteins in the human proteome (4,6,7,12,13,15), whilst large scale LC-MS/MS characterizations of methylation in other organisms (5, 8 -11, 14, 16) have reinforced the notion that these modifications are widespread and sometimes conserved in eukaryotes (summarized in Table I). …”
mentioning
confidence: 99%